Food on the go : Delights Bakery / Allyssa Andrew... [et al.] - Andrew, Allyssa; Alexander, Arvosrye; Miun, Ebelinah; Banting, Ernest Sylvester; Dee, Nowell Xavier; Jonathan, Yvonne (2014)
Food On The Go is a bakery shop located at Sulaman Central, Jalan Sulaman, Sepanggar, Kota Kinabalu Sabah that allow people with busy lifestyle to have their meals instantly and in the most convenient way. This product is suitable for all age ranged between children, teenagers and adults. Food on the Go sells various types of bakery products such as slice cakes, cupcakes and muffins and many more. Our shop is able to serve numbers of people such as entire family in one quick, convenient visit. We realized that there are many other bakery shop like Food on the Go, but we are very confident that we will excel due to its attention to detail regarding customer service. Food on the Go will slowly but surely gain market share as it is potentially for having a long term relationship with the customers, especially the families. Lastly, our advertisement's creativity will attract a lot of walk in traffic. Due to nowadays society's lifestyle, many people will go busy with their works and may not have the luxury for having their meals on crowded shops. But Food on the Go focus on the convenience for the customer to get their food, let alone the delicious healthy food. We have seen this opportunity because a lot of people with long working hours would go for fast food for their lunch and dinner because these shops serves their food in instant manners and efficient ways such as drive through and deliveries. But these foods are not very healthy due to its cooking nature (deep fried food). The strength of our shop is delivering healthy products in instant manners such as drive through and food delivery, and also efficient ways on our walk in services. We, Food on the Go, foresaw that our company has the potential of success provided that it is handled efficiently. Many people should go for healthier food in order to maintain their health and also, save more time to relax rather than lining up at a restaurant to get their food. We also provide services that are customer friendly to ensure return-customers and credibility from our customers. Food on the Go sees this as a way to prosper in this market, by taking advantage of these people's need.